Effects of the KiVa anti-bullying program on defending behavior: Investigating individual-level mechanisms of change - Garandeau Claire; Turunen Tiina; Saarento-Zaprudin Silja; Salmivalli Christina (Elsevier, 2025)
Given that defending victimized peers might help discourage bullying behavior and prevent its harmful consequences, various anti-bullying programs have attempted to increase defending behavior among participating children. However, the cognitions that underlie the effectiveness of interventions in increasing defending remain unknown. Data for this randomized controlled trial (RCT) of the KiVa anti-bullying program were collected in Finnish primary schools at baseline, after 5 months of implementation, and after 9 months of implementation and were used to examine the possible mediating role of seven psychological factors (empathy for the victim, feelings of responsibility to intervene, self-efficacy for defending, negative attitudes towards victims, and outcome expectations that defending would decrease or stop the bullying, be beneficial for one's status, and not increase one's risk of being victimized). Analyses conducted on a sample of 5731 children (baseline Mage = 11 years; 51% girls) revealed that the positive effects of KiVa on defending behavior after 9 months of implementation could partly be explained by the positive effects of the program on two factors (i.e., feelings of responsibility to intervene and expectations that the defending would make the bullying decrease or stop) after 5 months of implementation. This study provides information regarding the individual-level factors that anti-bullying interventions can target to successfully promote defending of victimized peers in primary schools.